Toward a conceptual framework and public policy agenda for the Information Society in Latin America and the Caribbean - Hilbert, Martin R. (ECLAC SantiagoCL, 2002)
Proposes a conceptual framework to discuss and analyze the complex issues and challenges related to the subject. Seeks to create an adequte policy agenda, considering the various particularities that the region confronts on its path into the digital age.